2018
DOI: 10.1016/j.addma.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emission for in situ quality monitoring in additive manufacturing using spectral convolutional neural networks

Abstract: HighlightsAn In situ quality monitoring for AM is presented Our approach combines acoustic emission with machine learning Fiber Bragg grating is used as acoustic sensors spectral convolutional neural networks is used for classification in terms of quality level The classification accuracy of the events ranged between 83 -89%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
132
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(135 citation statements)
references
References 21 publications
1
132
0
2
Order By: Relevance
“…Previous studies have shown that machine learning can be deployed for defect detection in the L-PBF process, using various techniques like acoustic sensors [34], thermal [36], grayscale [32], or high-resolution imaging [31]. While the current benchmarks range from 77 to 98% accuracy in detecting errors, they rely on either extensive data preprocessing or upon additional imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that machine learning can be deployed for defect detection in the L-PBF process, using various techniques like acoustic sensors [34], thermal [36], grayscale [32], or high-resolution imaging [31]. While the current benchmarks range from 77 to 98% accuracy in detecting errors, they rely on either extensive data preprocessing or upon additional imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the algorithm was at 77% and reduced experimental data are needed for training compared to supervised ML. Shevchik et al [34] and Ye et al [35] used acoustic signals for defect detection with ML. The acoustic signals need more data preparation before they can be used in algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…which, together with different fault categories, serve as input to train and test a deep CNN in terms of sideband amplitudes with an accuracy of 99.5%. Another successful approach that combines acoustic emission sensor signals converted to time-frequency spectrograms for real-time monitoring of the workpiece quality with CNNs was reported in [28]. The application of a hybrid feature extraction method combined with CNNs for tool condition monitoring was reported in [29], where signals from the dynamometer and accelerometer were independently subject to time-frequency transformation using Morlet wavelet transform and feature extraction using PyWavelets.…”
Section: Deep Learning In Condition Monitoringmentioning
confidence: 99%
“…The usage of sensors, allied with the digital signal processing to monitor the additive manufacturing processes, can be found in a large number of applications. For instance, acoustic emission (AE) sensors are applied in the monitoring of Selective Laser Melting (SLM) [3], Laser Metal Deposition (LMD) [4] and FDM manufacturing processes [2,5], as well as accelerometers are used for monitoring of FDM process [6].…”
Section: Introductionmentioning
confidence: 99%